Pengembangan Media Pembelajaran Komik Digital Menggunakan Model Addie pada Materi Keberagaman Budaya di Sekolah - Fatimah, Iis Daniati; Dwidarti, Fera; Wiratama, Novialita Angga; Mauliana, Siti (Universitas Muhammadiyah Magelang, 2026)
Cultural Diversity material is often considered complex due to the broad scope of information. Therefore, a digital comic medium is needed that can visualize the uniqueness of the archipelago's culture contextually, so that students not only memorize, but also feel an emotional closeness to the material. This study aims to develop a learning media in the form of digital comics on the topic of Cultural Diversity for fourth-grade students at Maibit Public Elementary School. The method used in this research is R&D (Research and Development) by applying the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The data analysis technique in this study uses quantitative descriptive to measure the results of teacher and student response questionnaires, as well as qualitative descriptive to describe and narrate feedback during the development process. The data obtained from the validation results show that the validation from media experts obtained a percentage of 96% with a valid category, content experts obtained a percentage of 94% with a valid category, and language experts obtained a percentage of 88% with a valid category. Based on the validation results from the experts, it shows that the digital comic media is declared valid. The practicality test conducted through teacher and student response questionnaires also shows a very practical category. The teacher response questionnaire results obtained a percentage of 96% with a practical category, and the student response questionnaire results obtained a percentage of 95% with a practical category. The effectiveness of digital comic learning media obtained a percentage of 92% with an effective category. Based on these research results, it can be stated that digital comic media can turn the learning situation into a more conducive and enjoyable environment, can improve learning outcomes, and digital comic learning media is feasible and practical to use.